(3TQM SbW GdRfOs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3GdHWdjhSj , YHO Gddg Hf eMeO Hf GdSjO, CHh eMeO,J (B521 (3g` s
(3ChdgG (B:s
(3CgGLc GdHQb HPGJ GdCeYR Hjf GdUQGg hGdaQGJ jLJRi s
(3BNQgG (B:s
(3eHJhQ hBNQ eGajg (B: (3LeLe gPG GdReGf bhdkG hcdfG jQJLi HjGfg MOKfG ddTjhN CeQkG heG GOYi eNHQ YjGfg s
(3ChQGbgG eVWQHI GdJQJjH (B_ (3hCUGH HYV CWQGagG JbWjYs
(3bWYI efg (B_ (3eQJHI Ydi GdbhGais
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B121s
Keywords: (3GdCOHs